2020
DOI: 10.1021/acs.analchem.0c01597
|View full text |Cite
|
Sign up to set email alerts
|

Sub-100 μm Spatial Resolution Ambient Mass Spectrometry Imaging of Rodent Brain with Laser Ablation Atmospheric Pressure Photoionization (LAAPPI) and Laser Ablation Electrospray Ionization (LAESI)

Abstract: In this study, we applied a new IR laser-beam-focusing technique to enable sub-100 µm spatial resolution in laser ablation atmospheric pressure photoionization (LAAPPI) and laser ablation electrospray ionization (LAESI) mass spectrometry imaging (MSI). After optimization of operational parameters, both LAAPPI-and LAESI-MSI with a spatial resolution of 70 µm produced high quality MS images, which allowed accurate localization of metabolites and lipids in the mouse and rat brain. Negative and positive ion LAAPPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…tissue sections). This is consistent with our earlier study showing similar spot-to-spot repeatability (RSD = 16.8%) with frozen tissue sections of rodent brain . The sampling of more geometrically complex trichome regions was more inconsistent.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…tissue sections). This is consistent with our earlier study showing similar spot-to-spot repeatability (RSD = 16.8%) with frozen tissue sections of rodent brain . The sampling of more geometrically complex trichome regions was more inconsistent.…”
Section: Resultssupporting
confidence: 92%
“…However, we recently showed that IRLA sampling can now ablate 20–40 μm diameter spots by using simple optics . We also demonstrated the use of this focusing method for MS imaging of rodent brain tissue sections with a 70 μm lateral resolution, showing that IR laser ablation APPI-MS (LAAPPI-MS) and laser ablation ESI (LAESI-MS) can now reach a new quality level in imaging rodent tissue . Thus, far, LAAPPI-MS has not been used to measure the contents of a single cell from tissue, whereas LAESI-MS has already shown its potential for single-cell analysis, for example, in a recent study with Allium cepa tissue …”
Section: Introductionmentioning
confidence: 99%
“…MAG (18:1), cholesterol, GalCer (d18:1/C24:1), and GalCer (d18:1/ C24:2) were mainly distributed in the corpus callosum, internal callosum, and less abundant in thalamus. [51][52][53][54] Creatine mainly distributed in brain areas except corpus callosum and glutamic acid was found to distribute in brain areas except corpus callosum, internal callosum, and hypothalamus.…”
Section: Imaging Of Pristine Mouse Brain Tissuementioning
confidence: 93%
“…Laser ablation techniques have also been applied to the analysis of murine tissues. LAAPPI and LAESI were recently utilized in the imaging of rodent brains 116 . A new infrared laser focusing technique was coupled with ambient mass spectrometry and applied to the analysis of lipids and other metabolites in dissected mouse brain samples, achieving tissue imaging with sub‐100 μm spatial resolution.…”
Section: Applications Of Ambient Ionization Mass Spectrometrymentioning
confidence: 99%